Mesenchymal stem cells protect CNS neurons against glutamate excitotoxicity by inhibiting glutamate receptor expression and function - Voulgari-Kokota, Androniki; Fairless, Richard; Diem, Ricarda (Experimental neurology, 2012)
Mesenchymal stem cells (MSC) promote functional recovery in experimental models of central nervous system (CNS) pathology and are currently being tested in clinical trials for stroke, multiple sclerosis and CNS injury. Their beneficial effects are attributed to the activation of endogenous CNS protection and repair processes as well as immune regulation but their mechanisms of action are poorly understood. Here we investigated the neuroprotective effects of mouse MSC in rodent MSC-neuron co-cultures and mice using models of glutamate excitotoxicity. A 24h pre-culture of mouse primary cortical neurons with MSC protected them against glutamate (NMDA) receptor-induced death and conditioned medium from MSC (MSC CM) was sufficient for this effect. Protection by MSC CM was associated with reduced mRNA levels of genes encoding NMDA receptor subunits, and increased levels for genes associated with non-neuronal and stem cell types, as shown by RT-PCR and cDNA microarray analyses. Changes in gene expression were not associated with alterations in cell lineage representation within the cultures. Further, MSC CM-mediated neuroprotection in rat retinal ganglion cells was associated with reduced glutamate-induced calcium influx. The adoptive transfer of EGFP+MSC in a mouse kainic acid epilepsy model also provided neuroprotection against glutamate excitotoxicity in vivo, as shown by reduced neuron damage and glial cell activation in the hippocampus. These results show that MSC mediate direct neuroprotection by reducing neuronal sensitivity to glutamate receptor ligands and altering gene expression, and suggest a link between the therapeutic effects of MSC and the activation of cell plasticity in the damaged CNS.